HISTORY OF ACUPUNCTURE FROM PAST TO PRESENT - Polat, E. (General Assoc Romanian Veterinarians, 2020)
Acupuncture is a treatment method based on stimulating special points on the body with various techniques. Acupuncture, one of the oldest medical sciences, has a history of about 5000 years. As a general opinion it is thought to be a Chinese origin treatment. However, some sources state that acupuncture was found by the Turks and developed by the Chinese. In this study, the development of acupuncture from past to present has been discussed.
Keywords: acupuncture; history; treatment